Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Menulis Cerpen di SMA Negeri 2 Kisaran - Halimatusa’diah Daulay; Siti Aisyah Hanim; Masithah Mahsa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the influence of the Discovery Learning Learning Model on the Ability to Write Short Stories at SMA Negeri 2 Kisaran..This type of research is all students off class XI science at SMA Negeri 2 range of 216 students. The sampling technique used in the data collection process is random sampling. Data analysis techniques using statistical analysis. Based on the results of research data analysis and hypothesis testing, it was concluded that the average result of the ability to write short stories in the XI IPA 2 experimental class taught using the discovery learning model obtained an average score of 87,88 higher tha the control class XI IPA 3 which obtained an average score of 81,88.